Identifying SNP threshold from P2 sequences for investigating norovirus transmission - Luqiu Tao; Xuan Wang; Yan Yu; Teng Ge; Hongjin Gong; Wei Yong; Jiali Si; Min He; Jie Ding (Virus Research, 2024)
Noroviruses are a group of non-enveloped single-stranded positive-sense RNA virus belonging to Caliciviridae family. They can be transmitted by the fecal-oral route from contaminated food and water and cause mainly acute gastroenteritis. Outbreaks of norovirus infections could be difficult to detect and investigate. In this study, we developed a simple threshold detection approach based on variations of the P2 domain of the capsid protein. We obtained sequences from the norovirus hypervariable P2 region using Sanger sequencing, including 582 pairs of epidemiologically-related strains from 35 norovirus outbreaks and 6402 pairs of epidemiologically-unrelated strains during the four epidemic seasons. Genetic distances were calculated and a threshold was performed by adopting ROC (Receiver Operating Characteristic) curve which identified transmission clusters in all tested outbreaks with 80 % sensitivity. In average, nucleotide diversity between outbreaks was 67.5 times greater than the diversity within outbreaks. Simple and accurate thresholds for detecting norovirus transmissions of three genotypes obtained here streamlines molecular investigation of norovirus outbreaks, thus enabling rapid and efficient responses for the control of norovirus.